Microdissection testicular sperm extraction–intracytoplasmic sperm injection strategy in patients with Klinefelter syndrome: synchronous or asynchronous? - Feng, Ke; Wang, Jin-Wei; Xia, Yan-Qing; Qu, Xiao-Wei; Wan, Feng; Zhang, Bo; Zhang, Cui-Lian; Guo, Hai-Bin; Feng, Lei-Lei; Fang, Ying-Hong (Frontiers in Endocrinology, 2025)
ObjectiveThe objective of this study was to compare the clinical outcomes of intracytoplasmic sperm injection (ICSI) with fresh versus cryopreserved sperm retrieved via microdissection testicular sperm extraction (mTESE) in patients with Klinefelter syndrome (KS).DesignA retrospective cohort study was conducted.SettingThis study was performed at the Reproductive Medicine Center of Henan Provincial People’s Hospital.ParticipantsA total of 260 men with KS, including 5 patients with mosaic KS, underwent mTESE,124 of whom successfully provided sperm. These patients were divided into synchronous (fresh sperm) and asynchronous (cryopreserved sperm) groups for ICSI treatment.InterventionsFresh or cryopreserved sperm were used in the ICSI cycles.Main outcome measuresThe primary outcomes were the clinical pregnancy rate, live birth rate, and miscarriage rate. The secondary outcomes were two pronuclei (2PN) embryos, available embryos, and the blastocyst formation rate. The number of oocytes retrieved and metaphase II (MII) oocytes were considered female-related indicators and treated as potential confounding variables in the multivariate analyses, given their influence on embryo development and pregnancy outcomes.ResultsA total of 260 KS patients underwent mTESE, with the successful retrieval of sperm suitable for ICSI in assisted reproduction from 124 (47.7%). Among these, 73 had their sperm cryopreserved at low temperature before ICSI, while 51 had their fresh sperm directly used for ICSI. The analysis of 170 treatment cycles revealed no significant differences in baseline characteristics (infertility duration, body mass index (BMI), follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone (T)) between the groups. Compared with the asynchronous group, the synchronous group had more oocytes retrieved, MII oocytes, gestational sacs, and good-quality embryos. However, there were no significant differences in 2PN embryos, 2PN fertilization rates, total embryos, available embryos, good-quality embryo rates, clinical pregnancy rates, live birth rates, or miscarriage rates between the two groups. LASSO regression and ROC curve analysis demonstrated the limited ability of differential indicators to predict pregnancy outcomes.ConclusionsIn KS patients undergoing ICSI, the use of fresh or cryopreserved testicular sperm did not significantly affect pregnancy outcomes. While fresh sperm have advantages in improving certain laboratory parameters, their overall ability to predict pregnancy outcomes is limited.